VALIDASI MEDIA PERMAINAN HOPSCOTH BERBASIS PENDIDIKAN KARAKTER UNTUK SISWA KELAS III SEKOLAH DASAR - Devi Ayu Mareta; Wendri Wiratsiwi (ELENOR: Elementary School Journal, 2022)
In schools the character education development program known as Strengthening Character Education (PPK) is still at the character introduction stage and has not been practiced well. This research aims to develop and validate character education-based hopscoth game media for third grade elementary school students. With the hopscoth game media, it is hoped that it will make it easier for students to understand the subject matter and can instill character values ​​so that they can be applied in everyday life. The method used in development research is the ADDIE model which consists of five stages, namely analyze, design, develop, implement, and evaluate. The product developed is a hopscoth game based on character education for third grade elementary school students. The data collection technique in this research is a questionnaire. The data collection instrument used was the validation sheet of material experts and media experts. The results of the calculation of the validation of the Hopscoth game media obtained 96% of material experts in the "valid" category and 87% from media experts in the "valid" category. These results indicate that the hopscoth game media is feasible and valid to be used for third grade elementary school students.